PENCEGAHAN BULLYING SISWA DISABILITAS DI SMAN 09 BOMBANA - Vanisa Syahrani; Muh. Ilham Syaputra; Ramlah; Nina Zakinah; Ayu Wandira; Rara; Kadirun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying remains a prevalent social problem in school environments, including at SMAN 09 Bombana, particularly affecting students with disabilities as a vulnerable group. Based on field observations and direct interactions, bullying occurs predominantly in verbal and social forms, often perceived as normal behavior among students. This study aims to identify the forms, impacts, and prevention efforts of bullying toward students with disabilities through socialization activities. The method used is a participatory counseling approach involving socialization, interactive discussions, case simulations, integration into classroom learning, and collaboration with the school and the Bombana Police Department. The results indicate that bullying still occurs in the form of mocking, negative labeling, excessive joking, and social exclusion. However, after the implementation of the program, there was a significant decrease in bullying cases and positive behavioral changes among students. Students demonstrated increased awareness, the ability to distinguish between jokes and bullying, improved empathy, and more inclusive social interactions. The involvement of teachers, parents, and the police contributed to strengthening both preventive and educational aspects, including legal awareness. Therefore, the socialization program is effective as an initial step in reducing bullying and creating a safe, inclusive, and supportive school environment. However, continuous and collaborative efforts are required to ensure sustainable prevention